Russian foreign policy management and manipulation with the Soviet successor states - Lutz, Carol K. G. (Terrorism and political violence, 2019)
Russia has been anxious to maintain its influence with the other successor states of the Soviet Union (the Near Abroad). It used a variety of methods, both overt and covert, to further its foreign policy objectives with these countries. Moscow has relied on traditional economic statecraft including trade manipulation, free trade arrangements, and currency linkages as well as ethnic appeals and propaganda/news manipulation to influence foreign audiences. In addition, Russia has used clandestine operations, including cyber attacks, and support for dissident groups. With the annexation of Crimea and the conflict with Georgia Russia chose direct military force because all other options had failed.